2021
DOI: 10.3389/fphys.2021.631850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Levels of Dietary Linseed Oil on the Growth Performance, Antioxidant Capacity, Hepatic Lipid Metabolism, and Expression of Inflammatory Genes in Large Yellow Croaker (Larimichthys crocea)

Abstract: A growth experiment was conducted to evaluate the effects of dietary fish oil (FO) replaced by linseed oil (LO) on the growth performance, antioxidant capacity, hepatic lipid metabolism, and expression of inflammatory genes in large yellow croaker (Larimichthys crocea). Fish (initial weight: 15.88 ± 0.14 g) were fed four experimental diets with 0% (the control), 33.3%, 66.7%, and 100% of FO replaced by LO. Each diet was randomly attributed to triplicate seawater floating cages (1.0 × 1.0 × 2.0 m) with 60 fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 70 publications
3
13
0
Order By: Relevance
“…It was reported that the total replacement of fish oil by vegetable oil significantly reduced the antioxidant capacity. Similar results have also been acquired in large yellow croaker (Li et al, 2021; Mu et al, 2018). Both dietary fish oil and optimum n‐3 LC‐PUFA content have been reported to promote antioxidant capacity across fish species (Jin et al, 2017; Puangkaew et al, 2005; Zuo et al, 2012) and mammals (Kirimlioglu et al, 2006).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was reported that the total replacement of fish oil by vegetable oil significantly reduced the antioxidant capacity. Similar results have also been acquired in large yellow croaker (Li et al, 2021; Mu et al, 2018). Both dietary fish oil and optimum n‐3 LC‐PUFA content have been reported to promote antioxidant capacity across fish species (Jin et al, 2017; Puangkaew et al, 2005; Zuo et al, 2012) and mammals (Kirimlioglu et al, 2006).…”
Section: Discussionsupporting
confidence: 85%
“…Replacing dietary fish oil by solo alternative lipids at high levels has been reported to affect the nonspecific parameters, antioxidant capacity and cytokine secretions in large yellow croaker (Li et al, 2021; Tan et al, 2016) and gilthead seabream (Montero et al, 2003). However, in some cases, no negative effect on immunity was reported with the inclusion of lipid blends at a certain level, such as in the previously mentioned species (Xu et al, 2015; Xue et al, 2006), yellow drum (Wabike et al, 2020) and yellow croaker (Mu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To gain additional insight into the regulation of lipid metabolism by dietary lipids in the liver, mRNA expression analyses related to lipid metabolism were conducted. Pgc1α has been shown to promote mitochondrial β-oxidation [39,53]. In this study, relative expression of pgc1α was significantly lower in medium and large turbot fed diets with L171.2 than those fed L120.7 diets.…”
Section: Discussionmentioning
confidence: 50%
“…In addition to growth performance, the physiological status has also been a focus of interest in fish nutrition research. One of the key indicators for the physiological status is the antioxidant capacity [39,40]. T-AOC directly reflected the antioxidant capacity of fish, while CAT and SOD are major antioxidant enzymes, which play an important role in removing reactive oxygen species (ROS), and MDA could indirectly reflect severity of cell impairment and oxidative stresses in fish [40].…”
Section: Discussionmentioning
confidence: 99%
“…Large yellow croaker (Larimichthys crocea) is an important marine fish in China due to its delicious taste and huge economic value [15][16][17]. Previous studies have assessed the effect of terrestrial-based lipid sources for larval and juvenile stages of large yellow croaker [18][19][20]. Up to now, no studies have been reported in large yellow croaker larvae to assess marine-based lipid sources as a potential replacement for FO in microdiets.…”
Section: Introductionmentioning
confidence: 99%